Human multipotent mesenchymal stem cells improve healing after collagenase tendon injury in the rat - Machova Urdzikova, Lucia; Sedlacek, Radek; Suchy, Tomas; Amemori, Takashi; Ruzicka, Jiri; Lesny, Petr; Havlas, Vojtech; Sykova, Eva; Jendelova, Pavla (Biomedical engineering online, 2014)
BACKGROUND: Mesenchymal stromal cells attract much interest in tissue regeneration because of their capacity to differentiate into mesodermal origin cells, their paracrine properties and their possible use in autologous transplantations. The aim of this study was to investigate the safety and reparative potential of implanted human mesenchymal stromal cells (hMSCs), prepared under Good Manufacturing Practice (GMP) conditions utilizing human mixed platelet lysate as a culture supplement, in a collagenase Achilles tendon injury model in rats. METHODS: Eighty-one rats with collagenase-induced injury were divided into two groups. The first group received human mesenchymal stromal cells injected into the site of injury 3 days after lesion induction, while the second group received saline. Biomechanical testing, morphometry and semiquantitative immunohistochemistry of collagens I, II and III, versican and aggrecan, neovascularization, and hMSC survival were performed 2, 4, and 6 weeks after injury. RESULTS: Human mesenchymal stromal cell-treated rats had a significantly better extracellular matrix structure and a larger amount of collagen I and collagen III. Neovascularization was also increased in hMSC-treated rats 2 and 4 weeks after tendon injury. MTCO2 (Cytochrome c oxidase subunit II) positivity confirmed the presence of hMSCs 2, 4 and 6 weeks after transplantation. Collagen II deposits and alizarin red staining for bone were found in 6 hMSC- and 2 saline-treated tendons 6 weeks after injury. The intensity of anti-versican and anti-aggrecan staining did not differ between the groups. CONCLUSIONS: hMSCs can support tendon healing through better vascularization as well as through larger deposits and better organization of the extracellular matrix. The treatment procedure was found to be safe; however, cartilage and bone formation at the implantation site should be taken into account when planning subsequent in vivo and clinical trials on tendinopathy as an expected adverse event.
Keywords: biomechanika; Wound Healing; Rats; Cell Differentiation; pluripotentní kmenové buňky; Mesenchymal Stem Cell Transplantation; Biomechanical Phenomena; Neovascularization, Physiologic; Carcinogenesis; Mesenchymal Stem Cells; transplantace mezenchymálních kmenových buněk; Collagenases; hojení ran; fyziologická neovaskularizace; krysa rodu Rattus; Extracellular Matrix; Osteogenesis; mezenchymální kmenové buňky; osteogeneze; Tendon Injuries; zvířata; Achilles Tendon; Humans; poranění šlachy; Pluripotent Stem Cells; buněčná diferenciace; kolagenasy; Achillova šlacha; karcinogeneze; extracelulární matrix; lidé; Animals